A case control study of serum vitamin D levels in alopecia areata - Naidu, Bobbili Tarun Kesava; Baddireddy, Kavya (International Journal of Research in Medical Sciences, 2020)
Background: Alopecia areata is an autoimmune disorder of anagen hair follicle leading to distressing and relapsing non-scarring hair loss. Vitamin D is an immunomodulator and plays a role in regulating normal hair cycle. Recent evidence suggests inconsistent association between vitamin D deficiency and alopecia areata. Methods: This case control study included 70 newly diagnosed cases of alopecia areata and 70 healthy controls. Competitive chemiluminescence immunoassay was used to determine and compare the serum vitamin D (25‑hydroxyvitamin D) levels between these groups. Also, the serum vitamin D levels correlation with severity of the disease was studied. ANOVA test and student t test were used for the statistical analysis. Results: Serum Vitamin D levels were significantly decreased in alopecia areata patients than in controls (p<0.05). There was no stastically significant relationship between serum 25-OH Vitamin D levels and severity of the disease (p=0.06). Conclusions: Prevalence of serum 25 (OH) deficiency was significantly higher in alopecia areata group. However no significant relation was found with disease severity.